2017
DOI: 10.1002/bmc.3971
|View full text |Cite
|
Sign up to set email alerts
|

A novel assay to determine acetylcholinesterase activity: The application potential for screening of drugs against Alzheimer's disease

Abstract: Acetycholinesterase (AChE) that regulates hydrolysis of acetylcholine (ACh) in the brain, is an important target for treatment of Alzheimer's disease (AD), a feature of which is ACh deficiency. However, the methods to precisely determine AChE activity are still under development. We developed a new method to exploit acetylcholine-d as a surrogate substrate of ACh and measure product choline-d via liquid chromatography-tandem mass spectrometry (LC-MS/MS). This assay detected activity of AChE present in the norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A comparative study between this UPLC-MS/MS method and the classic spectrometry method was performed. We analyzed the inhibitory activity of galantamine and extract of Drynariae Rhizome via this novel method and modified Ellman's method [23]. We found that both assays displayed identically dose-dependent effects of the two inhibitors on AChE activity.…”
Section: Comparison Of Uplc-ms/ms Methods and Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study between this UPLC-MS/MS method and the classic spectrometry method was performed. We analyzed the inhibitory activity of galantamine and extract of Drynariae Rhizome via this novel method and modified Ellman's method [23]. We found that both assays displayed identically dose-dependent effects of the two inhibitors on AChE activity.…”
Section: Comparison Of Uplc-ms/ms Methods and Spectrometrymentioning
confidence: 99%
“…Acetonitrile at 0°C demonstrated better repeatability than methanol and 1M HCL in terminating enzyme reaction. At the given concentration of AChE in reaction solution, the starting concentration of ACh-I was investigated, and 400 μg/mL was selected, which matched the Km value (Figure 3) [23].…”
Section: Optimization Of Ache Reaction Procedurementioning
confidence: 99%
“…The implementations of 3D printing technique in biochemical analyses have attracted enormous attention. , For instance, Salentijn et al developed a 3D-printed cartridge for paper spray ionization that can be used almost immediately after solvent introduction . With a careful design of the cartridge, spray lasted for tens of minutes, without any external pumping for mass spectrometry tests.…”
mentioning
confidence: 99%
“…To date, several analytical approaches have been developed for BuChE activity assay, such as electrochemical sensors, , fluorometry, ,, colorimetry, and chemiluminescent methods . MS analysis of BuChE was also investigated with pepsin-based immobilized enzyme microreactors. , Generally, the main obstacles of BuChE detection come from the tedious pretreatment and denaturing trend of BuChE activity during the detection.…”
mentioning
confidence: 99%
See 1 more Smart Citation